Members of the Candida parapsilosis Complex and Candida albicans are Differentially Recognized by Human Peripheral Blood Mononuclear Cells - Estrada-Mata, Eine; Navarro-Arias, María J.; Pérez-García, Luis A.; Mellado-Mojica, Erika; López, Mercedes G.; Csonka, Katalin; Gacser, Attila; Mora-Montes, Héctor M. (Frontiers in Microbiology, 2016)
The systemic infections caused by members of the Candida parapsilosis complex are currently associated to high mobility and mortality rates, and are considered as relevant as those caused by Candida albicans. Since the fungal cell wall is the first point of contact with the host cells, here we performed a comparison of this organelle in members of the C. parapsilosis complex, and its relevance during interaction with human peripheral blood mononuclear cells. We found that the wall of the C. parapsilosis complex members is similar in composition, but differs to that from C. albicans, with less mannan content and more β-glucan and porosity levels. Furthermore, lectin-based analysis showed increased chitin and β1,3-glucan exposure at the surface of C. parapsilosis sensu lato when compared to C. albicans. Yeast cells of members of the C. parapsilosis complex stimulated more cytokine production by human peripheral blood mononuclear cells than C. albicans cells; and this significantly changed upon removal of O-linked mannans, indicating this wall component plays a significant role in cytokine stimulation by C. parapsilosis sensu lato. When inner wall components were exposed on the wall surface, C. parapsilosis sensu stricto and C. metapsilosis, but not C. orthopsilosis, stimulated higher cytokine production. Moreover, we found a strong dependency on β1,3-glucan recognition for the members of the C. parapsilosis complex, but not for live C. albicans cells; whereas TLR4 was required for TNFα production by the three members of the complex, and stimulation of IL-6 by C. orthopsilosis. Mannose receptor had a significant role during TNF and IL-1β stimulation by members of the complex. Finally, we demonstrated that purified N- and O-mannans from either C. parapsilosis sensu lato or C. albicans are capable to block the recognition of these pathogens by human peripheral blood mononuclear cells. Together; our results suggest that the innate immune recognition of the members of the C. parapsilosis complex is differential of that reported for C. albicans. In addition, we propose that purified cell wall mannans can be used as antagonist to block specific receptors on innate immune cells.